ENHANCEMENT OF EMPLOYEE PERFORMANCE THROUGH QUALITY OF TECHNICAL ACADEMY AND SAFETY OF MEDAN AVIATION - Susi Diriyanti Novalina (UNIVERSITAS PEMBANGUNAN PANCA BUDI, 2019)
This study aims to determine the effect of employee performance on the implementation of promotions position in the Department of Youth and Sports in Medan City. This research uses a quantitative approach with survey research methods, namely research that takes samples from a population and uses the questionnaire as a primary data collection tool. The population of this research is all employees who work in the Medan Youth and Sports Agency. A number of samples used as many as 63 respondents. The results showed that employee performance has a significant effect positive about the promotion of the position, meaning that if the employee's performance is good then the employee can get a promotion. Thus the hypothesis that there is an influence on employee performance for promotion is acceptable. Keywords: Employee performance, and promotion